Rancangan Sistem Penyimpanan Arsip Surat Puskesmas Dengan Microsoft Access - Afifah Afifah; Eva Yoyet; Nila Agustin (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2022)
Archives are records of activities that serve as a source of information when making decisions. Over time, archive management in various agencies began to require electronics and advances in information technology. Likewise, with archives at the health center, their management already requires an electronic touch, so finding and utilizing them can be done quickly. Based on these needs, an archive storage system was designed for the Pauh Health Center, located in one of the sub-districts in the city of Padang. Archive storage system designed based on Microsoft Access; this application was chosen because it is relatively easy to learn and is an application that is included in Microsoft Office. The design of this system uses data from puskesmas archives from 2020 to 2022. The application design consists of: a login menu, incoming and outgoing mail tables, relations between tables, incoming and outgoing mail forms, incoming and outgoing mail reports, and switchboard menus. The weakness of this system design is that it has not been able to provide different access rights between admins and ordinary visitors. Another weakness is that the application can only be used internally at the health center and cannot be connected to the Padang City Health Office.